2021
DOI: 10.1029/2021jc017491
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variation of Modified Circumpolar Deep Water in the Dotson‐Getz Trough, West Antarctica

Abstract: In recent decades, Antarctic ice sheets have rapidly retreated, thus contributing to rising sea levels. An estimated 2720 billion tonnes of ice was lost from Antarctica between 1992 and 2017, corresponding to a global sea-level rise of about 7.6 mm (Shepherd et al., 2018). In particular, grounded ice reduction in West Antarctica accounted for ∼86% of the total Antarctic ice loss. The rapid ice reduction in West Antarctica caused by the increase in glacial flow is believed to be driven by the thinning of the bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 44 publications
(74 reference statements)
0
33
0
Order By: Relevance
“…St-Laurent et al (2015) and Webber et al (2017) emphasized the influence of local sea ice formation and air-sea heat fluxes on water temperatures over the Amundsen Sea continental shelf. Additionally, Kim et al (2021) found much larger variability in mCDW properties in the Dotson Trough close to the coast, as compared to at the shelf break. Warm and cold regimes in the Amundsen Sea have been identified using observations (e.g., Jenkins et al, 2018;Webber et al, 2017) and models (e.g., Dotto et al, 2019;Dutrieux et al, 2014;Nakayama et al, 2018).…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…St-Laurent et al (2015) and Webber et al (2017) emphasized the influence of local sea ice formation and air-sea heat fluxes on water temperatures over the Amundsen Sea continental shelf. Additionally, Kim et al (2021) found much larger variability in mCDW properties in the Dotson Trough close to the coast, as compared to at the shelf break. Warm and cold regimes in the Amundsen Sea have been identified using observations (e.g., Jenkins et al, 2018;Webber et al, 2017) and models (e.g., Dotto et al, 2019;Dutrieux et al, 2014;Nakayama et al, 2018).…”
mentioning
confidence: 78%
“…The results are similar if the average is calculated using the water column below the temperature maximum, so the latter is not presented here. We also tested using the mCDW layer thickness which has been demonstrated to be the main driver in heat content variability on the Amundsen Sea continental shelf (e.g., Jenkins et al., 2018 ; Kim et al., 2021 ; Thoma et al., 2008 ), but this approach gave similar results to the average temperature below 300 m, so is not presented here. In general, GLORYS has small regional temperature biases (<0.4 °C) in temperature with respect to the Worlds Ocean Atlas climatology 2013 and in situ data (Drévillon et al., 2021 ).…”
Section: The Glorys12v1 Reanalysis and Climatologymentioning
confidence: 99%
See 1 more Smart Citation
“…Ice shelf melt rates throughout West Antarctica vary over decadal ( 12 , 13 ), interannual ( 14 ), and seasonal ( 15 ) time scales. Modifications to the surface wind stress over the continental shelf break and their influence over heat transport onto the continental shelf have been cited as a key mechanism to explain variable melt rates at individual ice shelves, particularly in the Amundsen Sea ( 11 , 12 , 16 ). Numerical simulations indicate that the thickness of CDW, particularly in the eastern sector of the Amundsen Sea, responds on short, seasonal time scales to wind fluctuations ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ASL is a crucial driver of modern West Antarctic climate variability and controls the meridional winds directed toward West Antarctica (Hosking et al., 2013; Turner et al., 2013; Wang et al., 2020). Furthermore, variability of the ASL may play a role in accelerating glacial ice loss (Hosking et al., 2016), due to its influence on the heat budget (Dotto et al., 2020), the cavity circulation (Hattermann et al., 2021), the upwelling of warm CDW in polynyas (Kim et al., 2021), and the import of CDW beneath the ice shelves (Holland et al., 2019). All those processes could act to induce ocean‐forced ice‐sheet instability in this region.…”
Section: Discussionmentioning
confidence: 99%